OBSERVING THE PULSE OF THE FACULTY: NEEDS ASSESSMENT FOR THE FACULTY DEVELOPMENT PROGRAM - Alayon, Anna Fe S.; Sindol, Jr., Isauro S. (President University, 2024)
Higher education is not immune to the challenges posed by a society that is changing quickly. These problems strongly encourage universities to prioritize the caliber of their professors and provide adequate chances for professional growth. However, addressing the unique requirements, expertise, and objectives stated by the faculty actually boosts the effectiveness of any institutional faculty development program. Instruction, research, and extension form the triad of academic responsibilities that define the role of faculty in higher education institutions along with the faculty professional growth. Reputable and highly competent academic members are crucial to a university's goals. This descriptive study was conducted to assess the faculty development needs and priorities of the faculty at the West Visayas State University – Lambunao Campus. It includes the faculty needs in terms of instruction, research, extension, and professional development. A random sampling was employed involving 78 faculty members representing the respective department in the campus assessing the competency in instruction, engagement in research, and extension, and support for professional development. An adopted and researchers-made questionnaires, duly validated, were used as instruments. Frequency, mean, and standard deviation were used as statistical tools. The result of the study revealed that the faculty have a very high level of competence in terms of instruction but they have a low engagement in research and extension activities. Furthermore, the result showed that the faculty had a low level of support for professional development. Based on the results, a need for faculty development program should be crafted focusing in the needs for research and extension engagements as well as the program towards professional development.